Negotiating Emotional Order: - Jennifer A. Klimek Yingling (Grounded Theory Review: An International Journal, 2018)
In this article, classic grounded theory captures the processes of 12 women who had completed initial treatment for breast cancer. The qualitative data analysis reveals the basic social process of negotiating emotional order that describe how breast cancer survivors perceive their illness and decide to take action. From the data, five stages of the process of negotiating emotional order emerge: 1) Losing Life Order, 2) Assisted Life Order, 3)Transforming 4) Accepting, and 5) Creating Emotional Order. This study may help healthcare providers who care for breast cancer survivors understand the depth of perpetual emotional impact that breast cancer survivors endure. This study will potentially serve as a path for future research and aid in the understanding of the psychological impact that breast cancer has upon survivors.